2012
DOI: 10.1187/cbe.12-03-0026
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Test of Scientific Literacy Skills (TOSLS): Measuring Undergraduates’ Evaluation of Scientific Information and Arguments

Abstract: Life sciences faculty agree that developing scientific literacy is an integral part of undergraduate education and report that they teach these skills. However, few measures of scientific literacy are available to assess students’ proficiency in using scientific literacy skills to solve scenarios in and beyond the undergraduate biology classroom. In this paper, we describe the development, validation, and testing of the Test of Scientific Literacy Skills (TOSLS) in five general education biology classes at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
322
0
34

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(417 citation statements)
references
References 54 publications
5
322
0
34
Order By: Relevance
“…The research did not provide treatment, manipulation or alteration to the independent variables, but describes a condition as it is (Sukmadinata, 2012). Scientific literacy skills was known from the results of the science literacy test and then percentage of correct answers was analyzed according to the indicator adapted Gormally et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…The research did not provide treatment, manipulation or alteration to the independent variables, but describes a condition as it is (Sukmadinata, 2012). Scientific literacy skills was known from the results of the science literacy test and then percentage of correct answers was analyzed according to the indicator adapted Gormally et al (2012).…”
Section: Methodsmentioning
confidence: 99%
“…• Student Understanding of Science and Scientific Inquiry (SUSSI), an instrument developed by Liang et al (2008) Gormally, Brickman, & Lutz, 2012).…”
Section: Future Assessment Of the Projectmentioning
confidence: 99%
“…In [24] use the inquiry stages as a framework to develop scientific inquiry as scientific literacy assessment. Other researcher, [3] develop Test of Scientific Literacy Skills (TOSLS) with two main indicators, i.e., understand methods of inquiry that lead to scientific knowledge; and Organize, analyze, and interpret quantitative data and scientific information. In [7] found that scientific inquiry determines scientific literacy, but not on the amount of experience doing scientific inquiry, but on the quality of experience of conducting scientific inquiry.…”
Section: Introductionmentioning
confidence: 99%
“…The third-year student will graduation for next year, so that they can low scientific literacy we can propose the chaning of learning process to improve the ability of scientific literacy. The scientific literacy of biology student teachers were assess by using two instruments, based on -characteristic and step inquiry according [3,24], and the dimensions of scientific literacy by (Bybee, 2003) cited by [21].…”
Section: Introductionmentioning
confidence: 99%